Psychometric properties of the Chinese version of procrastination assessment scale for students - Yip, Michael C. W.; Chung, Olive L. L. (Frontiers in Psychology, 2022)
The procrastination assessment scale for students (PASS) has been used widely in evaluating the patterns of university students’ procrastination on academic tasks and their procrastination behavior. The present study validated the psychometric properties of a Chinese version of the PASS (PASS-C) by recruiting a representative sample of 1012 Hong Kong Chinese university students. The results confirmed that this modified Chinese version is a valid and appropriate tool to assess university students’ procrastination tendencies in Chinese educational settings.